Clay / polyether artificial composite solid electrolyte and preparation method and application thereof
Through the combined preparation method of modified clay and polyether, the clay isolation and compatibility problems in solid electrolytes are solved, efficient ion conduction and low impedance are achieved, and the electrochemical performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411493532.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing solid electrolytes have problems such as clay isolation, poor compatibility, uneven dispersion, slow ion transmission, and excessive impedance in batteries, which limit the performance of the battery.
The modified clay is prepared by combining polyether monomer by metal M ion intercalation and formula 1 graft modification process to improve ion conduction and clay compatibility.
It significantly improves the electrochemical performance of the composite solid electrolyte, reduces impedance, improves the ion transport capability and mechanical properties, and enhances the stability of the metal negative electrode.
Smart Images

Figure CN119495800A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of battery materials, and specifically relates to the field of solid electrolyte technology. Background Art
[0002] With the innovation of electric vehicles and energy storage systems, the demand for battery energy density continues to increase, and metal secondary batteries have emerged. Among them, lithium / sodium / potassium metal anodes have high theoretical specific capacity and low standard electrode potential (compared with standard hydrogen potential). Introducing them into the battery system is expected to further improve the battery energy density. However, during the entire electrochemical process of lithium / sodium / potassium charging and discharging, the uneven distribution of interfacial ion flow will cause obvious concentration polarization at the negative electrode interface, resulting in uncontrollable growth of dendrites and rupture of the SEI layer, which limits the further application of lithium / sodium / potassium metal anodes.
[0003] A stable solid interphase (SEI) is crucial for the development of next-generation high-energy-density metal batteries. Naturally formed SEI layers can optimize the interface between metal anodes and electrolytes, however, they are inherently non-uniform and brittle, which can easily lead to performance degradation and battery failure. For inorganic SEI, it has advantages such as excellent interfacial energy and superior ionic conductivity, which can accelerate the lateral diffusion of ions along the SEI / Li interface and effectively form a uniform ion flux, thereby inhibiting the formation of dendrites and improving the stability of metal anodes. However, the inherent stiffness of inorganic SEI leads to its low tolerance to the volume expansion of metal anodes, resulting in the fracture and failure of metal anodes during long-term battery cycling. Organic SEI has high volume change tolerance and superior SEI structural stability, which is conducive to the construction of high-quality composite SEI layers. However, the low ionic conductivity of organic SEI limits its development. Therefore, constructing an organic-inorganic composite artificial solid interphase layer to regulate the interface between metal and electrolyte is of vital importance for the cycling performance of metal anodes and the practical implementation of high-energy-density batteries.
[0004] There are also some reports on clay-organic solid electrolytes in the prior art. For example, Chinese patent document No. EP1171927A1 discloses microporous solid electrolytes and methods for preparing them, which records adding a certain clay component to the solid electrolyte. Chinese patent document No. CN117594871A also discloses a fully solid polymer composite electrolyte and a method for preparing it, which also records adding a clay component to the electrolyte.
[0005] In summary, although there are some solutions for adding clay to solid electrolytes in the prior art, the existing solutions still find it difficult to solve problems such as clay segregation, uneven dispersion due to poor compatibility, and excessive impedance due to slow ion transmission. Summary of the invention
[0006] In view of the problems existing in existing artificial composite solid electrolytes, the present invention provides a method for preparing a clay / polyether artificial composite solid electrolyte, aiming to provide a composite electrolyte with low impedance and excellent ion conductive properties.
[0007] The second purpose of the present invention is to provide a clay / polyether artificial composite solid electrolyte prepared by the preparation method and its application in solid-state batteries.
[0008] The third object of the present invention is to provide a solid-state battery and an electrode comprising the clay / polyether artificial composite solid electrolyte.
[0009] A method for preparing a clay / polyether artificial composite solid electrolyte, which is obtained by polymerizing a precursor solution containing a polyether monomer, a crosslinking agent, an initiator, an electrolyte salt, and a modified clay;
[0010] The modified clay is first intercalated with metal M ions and then grafted with formula 1;
[0011] The metal M includes at least one of Li, Na and K;
[0012]
[0013] The R1 is a C1-C6 alkyl group; the R2 is a substituted alkyl group with a substituent; the substituent includes at least one of an amino group, an epoxy group, a mercapto group, an acryloxy group, a vinyl group, and an isocyanate group.
[0014] The present invention innovatively uses the modified clay to prepare a clay / polyether artificial composite solid electrolyte in combination with a polyether monomer. The present invention's research shows that based on the combination of the special intercalation-formula 1 secondary modification process, further combined with the polyether, ion conduction can be improved, clay segregation problems can be improved, and thus the electrochemical performance of the composite solid electrolyte can be significantly improved.
[0015] In the present invention, clay is placed in a modified aqueous solution containing metal M ions for intercalation treatment to obtain an intercalation modified material, and then the intercalation modified material is placed in a solution of formula 1 for graft modification to obtain the modified clay.
[0016] In the present invention, through the combination of the metal M ion intercalation and the coating of Formula 1, it can be combined with the polyether to improve the ion conduction rate and pathway, thereby improving its electrochemical performance.
[0017] In the present invention, the clay comprises at least one of kaolinite, halloysite, illite, montmorillonite, hydromica, glauconite, chlorite, vermiculite, sepiolite, halloysite, bentonite and rectorite.
[0018] In the present invention, the metal M ion is provided by at least one raw material selected from the group consisting of lithium chloride, lithium acetate, lithium hydroxide, lithium bromide, lithium iodide, sodium chloride, sodium acetate, sodium hydroxide, sodium bromide, sodium iodide, potassium chloride, potassium acetate, potassium hydroxide, potassium bromide and potassium iodide.
[0019] Preferably, the metal M ions include two or more of Li, Na and K. Studies have shown that the combination of the composite ions can form a liquid alloy during charge and discharge, which helps to further enhance the ion conduction rate and pathway, and can further synergistically enhance the electrochemical properties of the material.
[0020] Further preferably, in the present invention, sodium ions are preliminarily used to perform a first intercalation on clay, and then lithium ions are used to perform a second intercalation on the product of the first intercalation to obtain the intercalation modified material. The present invention shows that the two-stage intercalation treatment of first sodium and then lithium can further optimize the physicochemical structure of the material, further improve its combined synergy with Formula 1, and further enhance the material performance.
[0021] Preferably, in the modified aqueous solution, the concentration of the metal M ion is 0.1 to 4 mol / L, further can be 1 to 3M; further can be 2 to 2.5M.
[0022] Preferably, the solid-liquid ratio in the intercalation modification stage is 0.1 to 2 g / ml, and can further be 0.5 to 1 g / mL.
[0023] Preferably, the temperature in the intercalation modification stage is 15-180°C, and further can be 70-90°C.
[0024] Preferably, the intercalation modification time is 1 to 72 hours, for example, 10 to 30 hours; further, 20 to 25 hours.
[0025] In the present invention, the compound of formula 1 includes compounds with the following structures:
[0026]
[0027]
[0028] The R3 is a saturated carbon chain of C1 to C6; and the R4 is an alkyl group of C1 to C6.
[0029] Preferably, the compound of formula 1 is selected from formula 1b and / or formula 1d, and more preferably is a composite of formula 1b and formula 1d. In the present invention, in the composite, the weight ratio of formula 1b to formula 1d can be 1:0.5-2. The present invention shows that the combination of formula 1d and formula 1d can be further combined with the intercalation modification process to further enhance the low impedance and performance of the material.
[0030] Preferably, the weight ratio of the compound of formula 1 to the clay is 0.1 to 1:1; further, it may be 0.2 to 0.5:1.
[0031] Preferably, the weight ratio of the modified clay to the polyether monomer is 0.1% to 50%, further 1 to 15%, and even further 5 to 10%.
[0032] In the present invention, the polyether monomer includes at least one of 1,3-dioxolane (DOL), 1,3,5-trioxane, 1,3,5-trioxane, 1,3-dioxane, 1,4-dioxane, 1,2-epoxycyclopentene, 3,4-epoxy-1-butene, propylene oxide, 2-trifluoromethyl ethylene oxide, glycidyl 2,2,3,3-tetrafluoropropyl ether, tetrahydrofuran, methyltetrahydrofuran, tetrahydropyran, fluoroethylene carbonate, and vinylene carbonate.
[0033] Preferably, the initiator includes at least one of lithium hexafluorophosphate, aluminum trifluoromethanesulfonate, stannous octoate, azobisisobutyronitrile, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium hexafluoroarsenate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium hexafluoroarsenate, potassium fluoroborate, potassium hexafluorophosphate, boron trifluoride, and phosphorus pentafluoride.
[0034] The concentration of the initiator in the polymerization monomer is 0.1-1M, preferably 0.4-0.8M.
[0035] Preferably, the cross-linking agent includes at least one of pentaerythritol glycidyl ether, trimethylolpropane triglycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, trimethylolpropane allyl ether, tert-butyl glycidyl ether, ethyl glycidyl ether, polypropylene glycol diglycidyl ether, isopropyl glycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, and ethylene glycol diglycidyl ether.
[0036] Preferably, the crosslinking agent is 0.2-15% by weight of the polyether monomer, preferably 0.5-1.5%.
[0037] Preferably, the electrolyte salt is at least one of a conductive lithium salt, a conductive sodium salt, and a conductive potassium salt.
[0038] Preferably, in the precursor solution, the concentration of the electrolyte salt is 0.1-4M, preferably 1-3M.
[0039] The invention also provides a clay / polyether artificial composite solid electrolyte prepared by the preparation method.
[0040] The preparation method described in the present invention can give the prepared material special physical and chemical characteristics, and the material prepared by the preparation method can improve the transfer path and rate of active ions, avoid material segregation, reduce the impedance of the material, and thus significantly improve the electrochemical performance of the prepared material.
[0041] The present invention also provides a positive electrode and / or a negative electrode composited with a solid electrolyte, wherein the solid electrolyte comprises a clay / polyether artificial composite solid electrolyte obtained by the preparation method.
[0042] In the present invention, the clay / polyether artificial composite solid electrolyte can be compounded in a conventional positive electrode and / or negative electrode.
[0043] The present invention also provides a solid-state battery, comprising a positive electrode, a solid electrolyte and a negative electrode which are compounded in sequence, wherein the solid electrolyte is the clay / polyether artificial composite solid electrolyte.
[0044] In the present invention, the solid-state battery, in addition to comprising the clay / polyether artificial composite solid electrolyte of the present invention, may have conventional components and structural parts.
[0045] The present invention also provides a method for preparing a solid-state battery, which is obtained by compounding a positive electrode, a solid electrolyte and a negative electrode; the solid electrolyte is the clay / polyether artificial composite solid electrolyte;
[0046] Preferably, at least one of the positive electrode and / or the negative electrode is a positive electrode and / or a negative electrode compounded with the solid electrolyte;
[0047] Preferably, the preparation method of the solid-state battery described in the present invention is an in-situ preparation method, the steps of which are: loading the battery cell composited with the positive electrode and the negative electrode into the battery shell, followed by liquid injection and packaging and in-situ polymerization, characterized in that the solution injected in the liquid injection stage is the precursor solution recorded in the preparation method.
[0048] In the present invention, the positive electrode and / or negative electrode is the positive electrode and / or negative electrode of the composite solid electrolyte described in claim 8.
[0049] Beneficial Effects
[0050] 1. The present invention is innovatively based on the combination of the intercalation-formula 1 secondary grafting modification process, and further combined with the polyether, which can improve ion conduction, improve clay segregation, poor compatibility and other problems. The clay / polyether artificial composite solid electrolyte of the present invention has high ion transmission capacity, desolvation structure, good mechanical properties, can promote uniform ion deposition, inhibit dendrite growth, and can greatly improve the air stability of the metal negative electrode.
[0051] 2. The clay / polyether artificial composite solid electrolyte of the present invention can protect the negative electrode of the metal secondary battery, and the preparation method is simple to operate and the conditions are mild. It can effectively improve the interface stability of the electrode / electrolyte while improving the conductivity and mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is the SEM image of the clay ore before modification in Example 1;
[0053] Figure 2 This is the SEM image of the clay ore after modification in Comparative Example 1;
[0054] Figure 3 This is the EIS diagram of the solid electrolyte lithium metal symmetric battery in Example 1. DETAILED DESCRIPTION
[0055] The following examples are intended to further illustrate the present invention in detail, but are not intended to limit the scope of protection of the claims of the present invention.
[0056] The optional clay modification method of the present invention comprises the following steps:
[0057] (1) The clay is immersed in a solution of metal salt A and subjected to intercalation treatment to obtain a first modified clay.
[0058] (2) Soaking the first modified clay in a solution containing Formula 1 and stirring the solution evenly to obtain modified clay.
[0059] The solution of the metal salt A is selected from one or more of lithium chloride, lithium acetate, lithium hydroxide, lithium bromide, lithium iodide, sodium chloride, sodium acetate, sodium hydroxide, sodium bromide, sodium iodide, potassium chloride, potassium acetate, potassium hydroxide, potassium bromide, and potassium iodide. The concentration of the selected metal salt is 0.1 to 4 mol / L.
[0060] The stirring time of step (1) is 1 to 72 hours, and the heating temperature is 15 to 180° C., preferably 35 to 100° C.
[0061] The optional method for preparing the clay / polyether artificial composite solid electrolyte of the present invention comprises the following steps:
[0062] Step 1: Stirring and mixing the prepared polyether monomer, crosslinking agent, initiator, electrolyte salt and modified clay together to form a composite solid electrolyte precursor solution;
[0063] Step 2: The precursor liquid is formed into a liquid film on the electrode surface by means of hot shearing, casting, filtration, spin coating, spraying and other technical means, and then in situ polymerized on the electrode surface to obtain an artificial composite solid electrolyte interface protection layer with a thickness of 10nm-20μm.
[0064] The polyether monomer is selected from any one or more of the following: 1,3-dioxolane (DOL), 1,3,5-trioxane, 1,3,5-trioxane, 1,3-dioxane, 1,4-dioxane, 1,2-epoxycyclopentene, 3,4-epoxy-1-butene, propylene oxide, 2-trifluoromethyl ethylene oxide, glycidyl 2,2,3,3-tetrafluoropropyl ether, tetrahydrofuran, methyltetrahydrofuran, tetrahydropyran, fluoroethylene carbonate, vinylene carbonate and derivatives thereof.
[0065] The polymerization initiator is selected from at least one of lithium hexafluorophosphate, aluminum trifluoromethanesulfonate, stannous octoate, azobisisobutyronitrile, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium hexafluoroarsenate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium hexafluoroarsenate, potassium fluoroborate, potassium hexafluorophosphate, boron trifluoride, and phosphorus pentafluoride.
[0066] The polymerization initiator is selected from at least one of lithium hexafluorophosphate, aluminum trifluoromethanesulfonate, and lithium difluorooxalate borate. The content of the initiator is 0.1-15 wt%.
[0067] The electrolyte salt is selected from at least one of bis(trifluoromethanesulfonyl)imide lithium, lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalate borate), lithium bis(fluorooxalate borate), lithium difluorobis(oxalate phosphate), lithium difluorophosphate, lithium hexafluoroarsenate, sodium bis(trifluoromethanesulfonyl)imide, sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium bis(fluorosulfonyl)imide, sodium bis(oxalate borate), sodium bis(fluorooxalate borate), sodium difluorobis(oxalate phosphate), sodium difluorophosphate, sodium hexafluoroarsenate, potassium bis(fluorosulfonyl)imide, potassium fluoroborate, potassium hexafluorophosphate, and potassium perchlorate. The selected electrolyte salt concentration is 0.1 to 4M.
[0068] The content of the modified clay is 0.01-50wt%.
[0069] The cross-linking agent includes at least one of pentaerythritol glycidyl ether, trimethylolpropane triglycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, trimethylolpropane allyl ether, tert-butyl glycidyl ether, ethyl glycidyl ether, polypropylene glycol diglycidyl ether, isopropyl glycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, and ethylene glycol diglycidyl ether. The cross-linking agent is 0.01 to 20 wt %, preferably 0.5 to 5 wt %, and further 0.5 to 1.5 wt % of the weight of the ether-containing monomer.
[0070] The precursor solution is polymerized in situ on the electrode surface to form a film at a temperature of 25-80° C. and a time of 1-72 hours.
[0071] In addition, the solution described in the present invention is not only applicable to lithium metal negative electrodes, but also to any one of sodium metal or potassium metal negative electrodes.
[0072] Example 1
[0073] A clay / polyether artificial composite solid electrolyte, wherein the in-situ polymerization monomer is 1,3-dioxolane (DOL) with a basic cyclic ether structure, the lithium salt is lithium bis(fluorosulfonyl)imide (LiTFSI), the in-situ polymerization initiator is lithium difluorooxalatoborate (LiDFOB), and the nano-clay mineral is vermiculite.
[0074] Step (A): The preparation method of modified vermiculite nanoclay is:
[0075] (A-1) vermiculite is heated and stirred in a 2 mol / L intercalation modification solution (LiCl aqueous solution in this case) (solid-to-liquid ratio of 0.5-1 g / mL) for 24 h at a heating temperature of 80° C. to obtain a first modified material;
[0076] (A-2) Then the first modified material is added to 5 wt% of Formula 1 (in this case, Formula 1A ( The aqueous solution of the mixture (formula 1) (0.4 times the weight of the clay) was stirred for 1.0 h in a water bath at 70° C. to obtain modified clay.
[0077] Step (B): preparing a composite solid electrolyte in an argon glove box (oxygen content is less than 0.05 ppm, water content is less than 0.01 ppm), and the preparation method is as follows:
[0078] 1) Firstly, the main lithium salt lithium bis(fluorosulfonyl)imide (LiTFSI) is dissolved in the in-situ polymerized monomer DOL to form a basic electrolyte; the lithium salt concentration in the basic electrolyte is 1.5 mol / L;
[0079] 2) based on the mass of the in-situ polymerized monomer, dispersing 5 wt% of the modified clay by weight of the monomer and 1 wt% of the cross-linking agent polyethylene glycol diglycidyl ether by weight of the monomer in the basic electrolyte to form a mixed solution;
[0080] 3) Based on the volume of the in-situ polymerization monomer, 0.5 mol / L of in-situ polymerization initiator lithium difluorooxalatoborate (LiDFOB) was added and dispersed in the mixed solution to obtain an in-situ polymerization precursor solution.
[0081] 4) The precursor liquid is sprayed on the surface of the lithium metal to form a liquid film, and then polymerized at room temperature for 1 to 5 days, that is, in situ polymerization is performed on the surface of the lithium metal negative electrode to obtain a composite artificial solid electrolyte interface protection layer (modified lithium metal negative electrode).
[0082] 5) Impedance test:
[0083] In a glove box, two pieces of modified lithium metal were composited as electrodes, and then the electrolyte precursor solution was injected, packaged, and in-situ cured (cured at room temperature for 3 to 4 days) to form a CR2025 button-type symmetrical battery. The battery was then placed at 25°C to measure the interface impedance.
[0084] The electrolyte precursor solution is the in-situ polymerization precursor solution lacking modified clay in step B-3).
[0085] The interfacial impedance of the lithium metal symmetric battery is 55.3Ω.
[0086] Example 2
[0087] Compared with Example 1, the only difference is that the clay mineral is replaced by montmorillonite, and the other operations and parameters are the same as those in Example 1.
[0088] The interface impedance of the assembled lithium metal symmetric battery is 59.4Ω.
[0089] Example 3
[0090] Compared with Example 1, the only difference is that the intercalation method of step (A-1) is changed. The experimental groups are:
[0091] Group A: Na-first-Li double intercalation scheme, the steps are: first heating and stirring the vermiculite in 2 mol / L NaCl for 12 h at a heating temperature of 80°C, and then heating and stirring it in 2 mol / L LiCl for 12 h at a heating temperature of 80°C to obtain the first modified material; other operations and parameters are the same as in Example 1.
[0092] Group B: Na-Li one-pot intercalation scheme, the steps of which are: heating and stirring vermiculite in a solution of NaCl and lithium chloride with a solute concentration of 2 mol / L (the molar ratio of sodium chloride and lithium chloride in the solute is the same) for 24 h at a heating temperature of 80°C to obtain a first modified material; other operations and parameters are the same as in Example 1.
[0093] The test results are:
[0094] Group A: The interface impedance of the assembled lithium metal symmetric battery is 52.6Ω.
[0095] Group B: The interface impedance of the assembled lithium metal symmetric battery is 56.8Ω.
[0096] Example 4
[0097] Compared with Example 1, the only difference is that the formula 1 in step A-2 is changed, and the experimental groups are:
[0098] Group A: Formula 1 is Formula 1d, and its structure is:
[0099] Group B: Formula 1 is Formula 1a and Formula 1d in a weight ratio of 1:1;
[0100] The weight and other operations and parameters of Formula 1 are the same as those of Example 1.
[0101] The test results are:
[0102] Group A: The interface impedance of the assembled lithium metal symmetric battery is 55.7Ω;
[0103] Group B: The interface impedance of the assembled lithium metal symmetric battery is 53.9Ω.
[0104] Example 5
[0105] A clay / polyether artificial composite solid electrolyte, wherein the in-situ polymerization monomer is 1,3,5-trioxane (DOX) with a basic cyclic ether structure, the lithium salt is lithium bis(fluorosulfonyl)imide (LiTFSI), the in-situ polymerization initiator is lithium difluorooxalatoborate (LiDFOB), and the nano-clay mineral is vermiculite.
[0106] Step (A): The preparation method of modified vermiculite nanoclay is:
[0107] (A-1) vermiculite was heated and stirred in 2.5 mol / L LiCl for 20 h at a heating temperature of 75° C. to obtain a first modified material;
[0108] (A-2) Then the first modified material is added to 10 wt% of Formula 1A ( The mixture was stirred in a water bath at 70° C. for 1.5 h to obtain modified clay.
[0109] Step (B): preparing a composite solid electrolyte in an argon glove box (oxygen content is less than 0.05 ppm, water content is less than 0.01 ppm), and the preparation method is as follows:
[0110] 1) Firstly, the main lithium salt lithium bis(fluorosulfonyl)imide (LiTFSI) is dissolved in the in-situ polymerized monomer DOL to form a basic electrolyte; the lithium salt concentration in the basic electrolyte is 1.25 mol / L;
[0111] 2) based on the volume and mass of the in-situ polymerized monomer, 10 wt.% of the modified clay by monomer weight and 1 wt.% of the cross-linking agent polyethylene glycol diglycidyl ether by monomer weight are dispersed in the basic electrolyte to form a mixed solution;
[0112] 3) Based on the volume of the in-situ polymerization monomer, 0.75 mol / L of in-situ polymerization initiator lithium difluorooxalatoborate (LiDFOB) was added and dispersed in the mixed solution to obtain an in-situ polymerization precursor solution.
[0113] 4) The precursor liquid is sprayed on the electrode surface to form a liquid film, and then polymerized at room temperature for 1 to 5 days, that is, in-situ polymerization is performed on the electrode surface to obtain a composite artificial solid electrolyte interface protection layer.
[0114] The interface impedance of the assembled lithium metal symmetric battery is 60.2Ω.
[0115] Example 6
[0116] Compared with Example 1, the only difference is that in step B-5), the injected electrolyte precursor solution is the in-situ polymerization precursor solution of step 3), and the other operations and parameters are the same as in Example 1.
[0117] The interfacial impedance of the lithium metal symmetric battery is 51.4Ω.
[0118] Comparative Example 1
[0119] Compared with Example 1, the only difference is that step A is missing, and in step B, the modified clay is replaced by vermiculite before modification, and other operations and parameters are the same as in Example 1.
[0120] The interface impedance of the assembled lithium metal symmetric battery is 102.7Ω.
[0121] Comparative Example 2
[0122] Compared with Example 1, the only difference is that the clay is only subjected to grafting modification of Formula 1 without intercalation modification, that is, in step A-1 of step A, the intercalation modification solution is changed to water, lacking lithium chloride solute, and other operations and parameters are the same as in Example 1.
[0123] The interface impedance of the assembled lithium metal symmetric battery is 93.9Ω.
[0124] Comparative Example 3
[0125] Compared with Example 1, the only difference is that the clay is only intercalated and modified, and the grafting modification of Formula 1 is missing, that is, in Step A-2 of Step A, Formula 1A is missing, and the other operations and parameters are the same as in Example 1.
[0126] The interface impedance of the assembled lithium metal symmetric battery is 85.4Ω.
[0127] Comparative Example 4
[0128] Compared with Example 1, the only difference is that in step A, the processing order of step A is changed. For example, vermiculite is first processed in step A-2, and then the obtained product is used as a raw material to process step A-1, and the obtained modified material is used as modified clay to process step B. Other operations and parameters are the same as in Example 1.
[0129] The interface impedance of the assembled lithium metal symmetric battery is 80.6Ω.
[0130] Comparative Example 5
[0131] Compared with Example 1, the only difference is that in step B-5, the original lithium sheet is used as the lithium metal negative electrode, the battery is assembled and tested, and the other operations and parameters are the same as in Example 1.
[0132] The interface impedance of the assembled lithium metal symmetric battery is 150.2Ω.
Claims
1. A method for preparing a clay / polyether artificial composite solid electrolyte, characterized in that: The method is obtained by polymerizing a precursor solution containing a polyether monomer, a cross-linking agent, an initiator, an electrolyte salt, and a modified clay; The modified clay is first intercalated with metal M ions and then grafted with formula 1; The metal M includes at least one of Li, Na and K; The R1 is a C1-C6 alkyl group; the R2 is a substituted alkyl group with a substituent; the substituent includes at least one of an amino group, an epoxy group, a mercapto group, an acryloxy group, a vinyl group, and an isocyanate group.
2. The method for preparing the clay / polyether artificial composite solid electrolyte according to claim 1, characterized in that: The clay is placed in a modified aqueous solution containing metal M ions for intercalation treatment to obtain an intercalation modified material, and then the intercalation modified material is placed in a solution of formula 1 for graft modification to obtain the modified clay.
3. The method for preparing the clay / polyether artificial composite solid electrolyte according to claim 1 or 2, characterized in that: The clay comprises at least one of kaolinite, halloysite, illite, montmorillonite, hydromica, glauconite, chlorite, vermiculite, sepiolite, halloysite, bentonite and rectorite.
4. The method for preparing the clay / polyether artificial composite solid electrolyte according to claim 1 or 2, characterized in that: The metal M ion is provided by at least one raw material selected from the group consisting of lithium chloride, lithium acetate, lithium hydroxide, lithium bromide, lithium iodide, sodium chloride, sodium acetate, sodium hydroxide, sodium bromide, sodium iodide, potassium chloride, potassium acetate, potassium hydroxide, potassium bromide, and potassium iodide; Preferably, in the modified aqueous solution, the concentration of metal M ions is 0.1 to 4 mol / L; Preferably, the solid-to-liquid ratio in the intercalation modification stage is 0.1 to 2 g / ml; Preferably, the temperature in the intercalation modification stage is 15 to 180°C; Preferably, the intercalation modification time is 1 to 72 hours; Preferably, the clay is preliminarily intercalated with sodium ions for the first stage, and then the product of the first stage intercalation is intercalated with lithium ions for the second stage to obtain the intercalation modified material.
5. The method for preparing the clay / polyether artificial composite solid electrolyte according to claim 1 or 2, characterized in that: The compounds of formula 1 include compounds with the following structures: The R3 is a C1-C6 saturated carbon chain; the R4 is a C1-C6 alkyl group; Preferably, the compound of formula 1 is formula 1b and / or formula 1d, and more preferably a complex of formula 1b and formula 1d; Preferably, the weight ratio of the formula 1 to the clay is 0.1 to 1:1; Preferably, the weight ratio of the modified clay to the polyether monomer is 0.1% to 50%.
6. The method for preparing the clay / polyether artificial composite solid electrolyte according to claim 1, characterized in that: The polyether monomer includes at least one of 1,3-dioxolane (DOL), 1,3,5-trioxane, 1,3,5-trioxane, 1,3-dioxane, 1,4-dioxane, 1,2-epoxycyclopentene, 3,4-epoxy-1-butene, propylene oxide, 2-trifluoromethyl oxirane, glycidyl 2,2,3,3-tetrafluoropropyl ether, tetrahydrofuran, methyltetrahydrofuran, tetrahydropyran, fluoroethylene carbonate, and vinylene carbonate; Preferably, the initiator comprises at least one of lithium hexafluorophosphate, aluminum trifluoromethanesulfonate, stannous octoate, azobisisobutyronitrile, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium hexafluoroarsenate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium hexafluoroarsenate, potassium fluoroborate, potassium hexafluorophosphate, boron trifluoride, and phosphorus pentafluoride; Preferably, the concentration of the initiator in the polymerization monomer is 0.1 to 1 M; Preferably, the cross-linking agent comprises at least one of pentaerythritol glycidyl ether, trimethylolpropane triglycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, trimethylolpropane allyl ether, tert-butyl glycidyl ether, ethyl glycidyl ether, polypropylene glycol diglycidyl ether, isopropyl glycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether and ethylene glycol diglycidyl ether; Preferably, the crosslinking agent is 0.2 to 15% by weight of the polyether monomer, preferably 0.5 to 1.5%; Preferably, the electrolyte salt is at least one of a conductive lithium salt, a conductive sodium salt, and a conductive potassium salt; Preferably, in the precursor solution, the concentration of the electrolyte salt is 0.1-4M.
7. A clay / polyether artificial composite solid electrolyte prepared by the preparation method according to any one of claims 1 to 6.
8. A positive electrode and / or negative electrode composited with a solid electrolyte, characterized in that: The solid electrolyte comprises a clay / polyether artificial composite solid electrolyte prepared by the preparation method according to any one of claims 1 to 6.
9. A solid-state battery, comprising a positive electrode, a solid electrolyte and a negative electrode which are compounded in sequence, characterized in that: The solid electrolyte is the clay / polyether artificial composite solid electrolyte as claimed in claim 7; Preferably, the solid-state battery comprises the modified electrode according to claim 8.
10. A method for preparing a solid-state battery, characterized in that: The positive electrode, the solid electrolyte and the negative electrode are composited to obtain; the solid electrolyte is the clay / polyether artificial composite solid electrolyte as claimed in claim 7; Preferably, at least one of the positive electrode and / or the negative electrode is the positive electrode and / or the negative electrode of the composite solid electrolyte as claimed in claim 8; Preferably, the preparation method of the solid-state battery of the present invention is an in-situ preparation method, which comprises the following steps: loading the battery cell composited with the positive electrode and the negative electrode into the battery shell, followed by liquid injection and packaging and then in-situ polymerization, characterized in that the solution injected in the liquid injection stage is the precursor solution described in any one of claims 1 to 6; Preferably, the positive electrode and / or negative electrode is the positive electrode and / or negative electrode of the composite solid electrolyte described in claim 8.
Citation Information
Patent Citations
Polymer composition containing heat stabilizer
CN101735629A
Method for preparing aniline copolymer and intercalation nanocomposite material of inorganic clay by mechanochemical polymerization method
CN103265697A
Method for preparing functional organic montmorillonite / SEBS nano composite material
CN104387716A
Halloysite nanotube modified polyurethane solid electrolyte, preparation method and battery thereof
CN110112458A
In-situ polymerization composite organic solid-state electrolyte and preparation method and application thereof
CN110233286A